The development of the financial market of the Republic of Kazakhstan in the context of globalization - Daribayeva, M. Zh. (Journal of Economic Research & Business Administration, 2015)
The article discusses the financial market of the Republic of Kazakhstan in the context of globalization. This paper promoted the concept of the interaction of the segments of the financial market and classification structure on instrumental grounds, based on the initiation of the idea of unity of the concept of “financial instrument” for any segment of the financial market. The influence of globalization processes and the formation of global financial markets led to the formation of specific financial instruments. Understanding their nature is necessary for effective risk management, pricing control, establishing an effective management and evaluation of the level of cooperation in the financial market. The study identified the need for a phased approach to the study of the complex interaction between segments of the financial market, the proposed unification of the indicators derived from them to calculate the value of GDP, a group of indicators of sustainable development. Clarify the role of globalization in the development of the financial market of the Republic of Kazakhstan.